2011
DOI: 10.1167/iovs.10-6357
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TLR4 Activation in Photoreceptor Mitochondrial Oxidative Stress

Abstract: Retinal photoreceptors are susceptible to mitochondrial oxidative stress/mtDNA damage in robust TLR4-mediated innate immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…Studies other than single nucleotide polymorphism analyses are needed to resolve this discrepancy. Additional evidence for the role of TLRs in retinal physiology and pathology has been reported (75)(76)(77)(78). Possible contributions of TLRs to the pathogenesis of neurodegeneration and heart disease have also been discussed (79,80), and endogenous ligands for these receptors have been identified (47,81).…”
Section: Rdh8mentioning
confidence: 99%
“…Studies other than single nucleotide polymorphism analyses are needed to resolve this discrepancy. Additional evidence for the role of TLRs in retinal physiology and pathology has been reported (75)(76)(77)(78). Possible contributions of TLRs to the pathogenesis of neurodegeneration and heart disease have also been discussed (79,80), and endogenous ligands for these receptors have been identified (47,81).…”
Section: Rdh8mentioning
confidence: 99%
“…activated in the apoptotic process and subsequently processes executioner caspases 3 (28,30). These steps are all essential for apoptosis induction.…”
mentioning
confidence: 99%
“…[31][32][33][34] Moreover, it has been reported that proinflammatory cytokines, such as transforming growth factor (TGF)-β1, interleukin (IL)-1β, and IL-6, were rapidly upregulated under ischemic conditions in astrocytes or Müllers cells, microglia, and endothelial cells in the retina in rat and mouse models. 35,36 TLR4 signaling activation might be connected with the upregulation of those proinflammatory or angiogenic cytokines.…”
mentioning
confidence: 99%